Optimal Hajj Funds Management by Islamic Bank - Ariani Dian Pratiwi; Idqan Fahmi; Rifki Ismal (ETIKONOMI, 2019)
The purpose of this paper is to find the optimal portfolio of Hajj fund management by the Islamic banks in Indonesia. BPKH, as an authority, can place the Hajj fund on Islamic bank deposits. However, Islamic banks limited the expected returns and risks set by BPKH so that the appropriate strategy is required to establish the optimal of portfolio. Islamic banks face a trade-off because of the increased level of risk constrains the intention to get higher returns. This study uses a mean-variance portfolio optimization theory to construct such an optimal portfolio. Finally, this study recommends Murabaha financing and SBIS to Islamic banks as the optimal portfolio selection. The combination of an efficient portfolio that has formed cannot be fully employed because the expectation limits them. However, Islamic banks can still select the optimal portfolio combination according to their risk preferences.JEL Classification: G11, G18